Challenges during pancreatoduodenectomy and ways to overcome them - F. Sh. Akhmetzyanov; A. G. Kotelnikov; M. D. Ter-Ovanesov; V. I. Egorov; T. D. Gostyunin; O. A. Karpeeva (Сибирский онкологический журнал, 2024)
Background. Pancreaticoduodenal resection (PDR) is the surgical procedure for cancer of the head of the pancreas, distal common bile duct, duodenum and ampulla of Vater. This surgery is associated with a high risk of complications, the development of which can be influenced by various factors. since pancreatic fistula is a key complication of PDR, the choice of the method for pancreatic anastomosis becomes especially important. Material and methods. The search for publications was carried out using the PubMed and Elibrary systems from January 1980 to January 2024. of the 2,300 sources found, 69 were used to write the review. We included data from both retrospective and prospective clinical trials that were devoted to pancreatoduodenectomy for malignant neoplasms, the difficulties encountered in performing this surgery and ways to solve them. Results. Currently, there are more than 60 types of pancreatico-digestive anastomosis, which indirectly indicates the absence of a universal one that ensures the prevention of pancreatic fistula. The treatment outcomes may be influenced by the nature of neoadjuvant treatment, concomitant diseases, anatomical features, presence of obstructive jaundice and methods of its relief. The main mechanisms of influence of negative factors on the development of complications are considered. an individual approach to the patient, taking into account all factors, can significantly reduce the risk of complications.